Softening of Temperate Ice by Interstitial Water - Adams, Conner J. C.; Iverson, Neal R.; Helanow, Christian; Zoet, Lucas K.; Bate, Charlotte E. (Frontiers in Earth Science, 2021)
Ice at depth in ice-stream shear margins is thought to commonly be temperate, with interstitial meltwater that softens ice. Models that include this softening extrapolate results of a single experimental study in which ice effective viscosity decreased by a factor of ~3 over water contents of ~0.01 to 0.8%. Modeling indicates this softening by water localizes strain in shear margins and through shear heating increases meltwater at the bed, enhancing basal slip. To extend data to higher water contents, we shear lab-made ice in confined compression with a large ring-shear device. Ice rings with initial mean grain sizes of 2-4 mm are kept at the pressure-melting temperature and sheared at controlled rates with peak stresses of ~0.06-0.20 MPa, spanning most of the estimated shear-stress range in West Antarctic shear margins. Final mean grain sizes are 8-13 mm. Water content is measured by inducing a freezing front at the ice-ring edges, tracking its movement inward with thermistors, and fitting the data with solutions of the relevant Stefan problem. Results indicate two creep regimes, below and above a water content of ~0.6%. Comparison of effective viscosity values in secondary creep with those of tertiary creep from the earlier experimental study indicate that for water contents of 0.2%-0.6%, viscosity in secondary creep is about twice as sensitive to water content than for ice sheared to tertiary creep. Above water contents of 0.6%, viscosity values in secondary creep are within 25% of those of tertiary creep, suggesting a stress-limiting mechanism at water contents greater than 0.6% that is insensitive to ice fabric development in tertiary creep. At water contents of ~0.6-1.7%, effective viscosity is independent of water content, and ice is nearly linear-viscous. Minimization of intercrystalline stress heterogeneity by grain-scale melting and refreezing at rates that approach an upper bound as grain-boundary water films thicken might account for the two regimes.